2015
DOI: 10.1186/s12906-015-0709-1
|View full text |Cite
|
Sign up to set email alerts
|

Oligonol suppresses lipid accumulation and improves insulin resistance in a palmitate-induced in HepG2 hepatocytes as a cellular steatosis model

Abstract: BackgroundOligonol is a low molecular weight form of polyphenol polymers derived from lychee fruits. Several studies suggest that Oligonol has an anti-obesity effect. Since obesity is tightly associated with insulin resistance, we investigated a possible remission effect of Oligonol on lipid accumulation and insulin resistance in human hepatic HepG2 cells.MethodsHepG2 cells were treated with palmitate for 24 h to induce cellular hepatic steatosis and insulin resistance. The cells were then treated with Oligono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 59 publications
5
36
0
Order By: Relevance
“…In this context, the possible molecular mechanism of oligonol in alleviating hepatic insulin resistance was through suppressed mTOR/S6K1 signaling pathway under the condition of nutrient overload. In line with our in vivo experiments, activation of AMPK, inhibition of mTOR/S6K1, and decreased serine phosphorylation by oligonol has been reported by palmitate induced‐insulin resistance in HepG2 hepatocytes . Selective inhibitors of PTEN and GSK3α have been shown to improve insulin sensitivity in animal models of diabetes and obesity .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this context, the possible molecular mechanism of oligonol in alleviating hepatic insulin resistance was through suppressed mTOR/S6K1 signaling pathway under the condition of nutrient overload. In line with our in vivo experiments, activation of AMPK, inhibition of mTOR/S6K1, and decreased serine phosphorylation by oligonol has been reported by palmitate induced‐insulin resistance in HepG2 hepatocytes . Selective inhibitors of PTEN and GSK3α have been shown to improve insulin sensitivity in animal models of diabetes and obesity .…”
Section: Discussionsupporting
confidence: 89%
“…Many recent studies further demonstrated that, similar to EGCG, oligonol inhibited adipogenesis via suppressing Akt/mTOR (mammalian target of rapamycin) and enhanced lipolysis via extracellular‐signal‐regulated kinases (ERK) activation in adipocytes . Furthermore, oligonol suppressed lipid accumulation via enhancing AMP‐activated protein kinase (AMPK) activation and inhibiting mTOR‐S6K (ribosomal protein S6 kinase) pathway in palmitate induced‐insulin resistance in HepG2 hepatocytes . In vitro evidence suggests that oligonol exhibits beneficial effects on obesity‐related metabolic disorders, however, no direct in vivo evidence systemically investigate the relationship between peripheral lipid metabolism and insulin resistance upon treatment with oligonol.…”
Section: Introductionmentioning
confidence: 99%
“…A,B). To determine whether this decrease occurred in hepatocytes, primary cells were isolated from wild‐type (WT) mice and stimulated with vehicle or PA, an inducer of lipid accumulation and IR in hepatocytes . Compared with vehicle‐treated cells, PA triggered a marked decrease in Dusp9 expression in hepatocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5C). Palmitate-induced lipid accumulation is generally used as a cellular steatosis model (31). To ascertain whether reduced autophagy in FNDC5 2/2 mice is involved in lipid accumulation, the effects of rapamycin and Atg5 siRNA on palmitate-induced lipid accumulation in primary hepatocytes were investigated.…”
Section: Rapamycin Repairs the Attenuated Autophagy In Fndc5 Deficiencymentioning
confidence: 99%